Computer Vision Syndrome in High School Students: The Role of Gadget Use Intensity - Gufraan, Ghathan; Said Munazar Rahmat (Sriwijaya Journal of Ophthalmology, 2024)
Introduction: The ubiquity of digital devices in the lives of high school students has raised concerns about the potential impact on their visual health. Computer vision syndrome (CVS), a constellation of eye and vision-related problems, has been linked to prolonged digital screen use. This study aimed to investigate the relationship between gadget use intensity and the prevalence and severity of CVS in high school students. Methods: A cross-sectional study was conducted involving a sample of high school students. Data on gadget use intensity (hours per day) and CVS symptoms were collected through validated questionnaires. The Computer Vision Symptom Scale (CVSS) was used to assess the severity of CVS. Statistical analyses were performed to examine the association between gadget use intensity and CVS prevalence and severity. Results: The study found a significant positive correlation between gadget use intensity and the prevalence and severity of CVS in high school students. Students who reported higher levels of gadget use were more likely to experience CVS symptoms and exhibit greater symptom severity. Conclusion: The findings underscore the importance of promoting healthy gadget use habits among high school students. Interventions aimed at reducing screen time and encouraging regular breaks may be crucial in mitigating the risk of CVS and its associated visual discomfort.